The catalytic deoxygenation reaction temperature and N2 gas flow rate influence the conversion of soybean fatty acids into Green Diesel - Hafriz, R.S.R.M.; Habib, S.H.; Raof, N.A.; Razali, S.Z.; Yunus, R.; Razali, N.M.; Salmiaton, A. (Taiwan Institute of Chemical Engineers, 2024)
Background: Green diesel is a promising alternative as a petroleum replacement given the worldwide demand for petroleum fuel. Environmental issues have drawn public attention and concerns towards advancing renewable energy development. A catalytic deoxygenation (deCOx) was carried out to produce green diesel from soybean oil (SO) using a low-cost NiO-doped calcined dolomite (NiO[sbnd]CD) catalyst. Method: The structure, chemical composition and morphology of NiO[sbnd]CD were comprehensively characterized by XRF, BET, TPD-CO2, SEM and TEM. In this study, the effect of two operating parameters, reaction temperature and flow rate of nitrogen, was discovered using a one-factor-at-a-time (OFAT) optimisation study. In addition, the life cycle cost analysis (LCCA) of stepwise catalyst preparation and green diesel production has been performed. Significant findings: An optimal reaction temperature of 420 °C was found to provide the highest yield of green diesel (47.13 wt.%) with an 83.51% hydrocarbon composition. The ideal nitrogen flow rate, however, was found to be 50 cm3/min, which produced 41.80 wt.% of green diesel with an 88.63% hydrocarbon composition. The deoxygenation reaction was significantly impacted by both reaction temperature and nitrogen flow rate. According to LCCA, NiO[sbnd]CD catalyst has potential to lower the overall cost of producing green diesel compared to commercial zeolite catalysts. © 2024